IDENTIFIKASI ETNOMATEMATIKA YANG TERDAPAT DALAM PEPATAH MASYARAKAT BENGKULU “ IKAN SEJEREK, BERE SECUPAK” - Dwi Yanti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— The purpose of this study is to Identify the ethnomatematics contained in the proverb of the community of Bengkulu